FROM POLICY TO PRACTICE: IMPLEMENTING NRP 2020 IN ASSAM'S HIGHER EDUCATION AND ROLE OF COLLEGE TEACHERS - Bharali, Amarjyoti (ShodhKosh: Journal of Visual and Performing Arts, 2024)
This article examines the role of NEP 2020 in transforming Assam's higher education sector, with an emphasis on Four year undergraduate college course (FYUGC). The discussion highlights the current challenges in Assam’s higher education system, such as infrastructure limitations, socio-economic factors, and language barriers, while aligning these with NEP's provisions. It focuses on the implementation of key reforms such as interdisciplinary education, the introduction of the Academic Bank of Credits, and the emphasis on research and innovation. The role of college teachers in facilitating these transitions is crucial, and their professional development is explored. The article outlines strategies for effective policy implementation, such as infrastructure development, faculty training, and leveraging digital tools. Recommendations are made for policymakers to tailor NEP 2020 to Assam’s unique needs, ensuring that the state's higher education system fosters inclusivity, research, and academic excellence.